Shallot—Allium cepa (Aggregatum group) - James M. Stephens (EDIS)
This document describes the shallot (Allium cepa, Aggregatum group), a perennial vegetable similar to the common onion. It explains the plant’s growth habit, including its production of clusters of small, pointed bulbs and hollow leaves. The document outlines cultivation practices suitable for Florida, emphasizing propagation by bulb division rather than seed. It also highlights recommended varieties, planting times, and harvesting guidelines. Shallots are valued for their mild flavor and versatility in fresh or cooked dishes. Original publication date May 1994.